Evaluation of various methods of methylene blue removal from the post space after photodynamic therapy on the bonding interface using different resin cementation systems - Alencar, Cristiane de Melo [UNESP]; Costa, Joatan Lucas de Sousa Gomes [UNESP]; Jassé, Fernanda Ferreira de Albuquerque; Campos, Edson Alves de [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2021)
Background: To evaluate the effects of three protocols for removing 0.01 % methylene blue from the post space after photodynamic therapy on bond strength and tag formation in the dentin of the fiber post space, using a conventional cementation system with an etch-and-rinse or universal adhesive system. Methods: Sixty human canines were endodontically treated for fiber post cementation. The specimens were randomized into 6 groups (n = 10): G1, G2, G3, G4, G5, and G6. The G1, G2, and G3 groups were irrigated with saline solution, 2.5 % sodium hypochlorite (NaOCl), and 2.5 % NaOCl, agitated by passive ultrasonic irrigation (PUI), respectively. In these groups, a conventional cementation system with etch-and-rinse adhesive was used. The G4, G5, and G6 groups were irrigated with the respective solutions mentioned above and cemented using a conventional cementation system with universal adhesive. Tag formation in the dentin was evaluated by confocal laser scanning microscopy. The push-out bond strength test was performed on three thirds of the specimens. Results: In the cervical and middle thirds, the greatest extent of dentin tag formation occurred in the G1 (p = 0.023 and p = 0.033, respectively). In the apical third, G1, G2, and G3 demonstrated similar tag formation between themselves (p = 0.089). In the cervical and middle thirds, G4 demonstrated the highest bond strength when compared to the other groups (p < 0.05). Conclusion: The protocols for removing 0.01 % methylene blue with NaOCl, irrespective of the involvement of passive ultrasonic irrigation, negatively effects the bond strength and tag formation in the dentin of the post space.
Keywords: Dental bonding; Fiber post; Methylene blue; Photodynamic therapy; Resin cements